3.49m-.107=.0943+3.22m

Simple and best practice solution for 3.49m-.107=.0943+3.22m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3.49m-.107=.0943+3.22m equation:


Simplifying
3.49m + -0.107 = 0.0943 + 3.22m

Reorder the terms:
-0.107 + 3.49m = 0.0943 + 3.22m

Solving
-0.107 + 3.49m = 0.0943 + 3.22m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-3.22m' to each side of the equation.
-0.107 + 3.49m + -3.22m = 0.0943 + 3.22m + -3.22m

Combine like terms: 3.49m + -3.22m = 0.27m
-0.107 + 0.27m = 0.0943 + 3.22m + -3.22m

Combine like terms: 3.22m + -3.22m = 0.00
-0.107 + 0.27m = 0.0943 + 0.00
-0.107 + 0.27m = 0.0943

Add '0.107' to each side of the equation.
-0.107 + 0.107 + 0.27m = 0.0943 + 0.107

Combine like terms: -0.107 + 0.107 = 0.000
0.000 + 0.27m = 0.0943 + 0.107
0.27m = 0.0943 + 0.107

Combine like terms: 0.0943 + 0.107 = 0.2013
0.27m = 0.2013

Divide each side by '0.27'.
m = 0.7455555556

Simplifying
m = 0.7455555556

See similar equations:

| -12y+-3=-15 | | 35y-49-8y+7= | | 8x+12+5x=-12+3x+30 | | 180-83= | | 1x=-2x | | 8x-32=4(x-4) | | 84=-7(3k+3) | | 2x*5=9x-2/5 | | (2n-3)+(n+4)= | | X-16=84 | | (7x)(6x)=5x(10x-4) | | 17x+9=4(4x+5) | | -5(6y-5)-y=-2(y-3) | | 3x+7=-3x+25 | | 5r+3= | | K/-3-3=-20 | | X/12=25 | | Z^2=8z+36 | | logx-log(x-8)=1 | | 5x+14=39 | | 1.03-0.62x=0.71-0.22 | | -12+a=7.15 | | 2x+6-4x=24 | | 12x+4+9x+2=90 | | X+52=38 | | 4y+7=17 | | 2x+6-4x=25 | | .4x-3.5=13.5 | | 9x-5x+7=x-6+13 | | 14+3u=2 | | 2f+6+9=13 | | 1.55t-2.85=8.5+10.85 |

Equations solver categories